Impurity segregation during growth of silicon single crystals - Головко, Юрій Вікторович (Technology audit and production reserves, 2012)
In article on the basis of experimental researches and the developed mathematical models it is shown, that the size of effective segregation coefficient of carbon impurity decreases at accumulation of carbon in silicon melt during crystallization